Characterization of polymicrobial biofilms obtained from saliva or carious lesions in dentin - Farias, Aline Leite de [UNESP]; Carvalho, Lorena Petrucelli Freire de [UNESP]; Méndez, Daniela Alejandra Cusicanqui; Cruvinel, Thiago; Brighenti, Fernanda Lourenção [UNESP] (Taylor & Francis, 2020)
This study aimed to compare the formation of polymicrobial biofilms using carious dentin or saliva as inoculum for application in in vitro microbiological studies on caries research. For biofilm growth, combined samples of infected dentin or saliva from three donors were used. The biofilms were grown on glass coverslips, under a regimen of intermittent exposure (6 h day−1) to 1% sucrose for 4 days. Total bacterial loads, as well as specific aciduric bacteria and mutans streptococci loads were quantified and correlated with biofilm acidogenicity and susceptibility to chlorhexidine. The data were evaluated using the Student’s-t, Mann Whitney and Kruskal-Wallis tests. The two biofilms showed similar microbial loads (total bacteria, aciduric bacteria and mutans streptococci) on day 4, and high acidogenicity after 48 h and were susceptible to chlorhexidine at different time intervals. In conclusion, both dentin and saliva can be used as an inoculum in in vitro studies of processes related to biofilm formation.
Keywords: Dental caries; infected dentin; polymicrobial biofilm; saliva